PENGARUH TRANSFER PRICING DAN CAPITAL INTENSITY TERHADAP TAX AVOIDANCE DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI PEMODERASI (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI) - Dina Meilisa Wati; Khasanah Sahara; Nur Rahmanti Ratih (Cahaya Ilmu Bangsa, 2025)
This research aims to examine the influence transfer pricing And capital intensity to tax avoidance with good corporate governance (GCG) as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange (BEI) during the 2019-2022 period. The research methods used are descriptive statistical analysis, classical assumption testing, and hypothesis testing with the help of SPSS software. The research results show that transfer pricing has a positive but not significant influence on tax avoidance. Likewise with capital intensity which also showed a non-significant negative influence on tax avoidance. In addition, GCG is unable to moderate the relationship between transfer pricing, capital intensity to tax avoidance. In conclusion, although there is a positive influence, the influence given by transfer pricing And capital intensity to tax avoidance which is not significant, and GCG weakens the influence of the variable transfer pricing, And capital intensity to tax avoidance. Suggestions for the government, this research can be used as material for further evaluation, increasing compliance in paying taxes. For company management, this research can be used as a consideration to pay more attention to decisions related to tax avoidance practices. As well as suggestions for further research, it is recommended to add other variables that might influence tax avoidance, it is recommended to test other sectors such as services and finance, and use more sophisticated analytical methods.